Evaluation of Some Plant Essential Oils against the Brown-banded Cock-roach, Supella longipalpa (Blattaria: Ectobiidae), A Mechanical Vector of Human Pathogens - Mona Sharififard; Farhad Safdari; Amir Siahpoush; Hamid Kassiri (Tehran University of Medical Sciences, 2016)
Background: Essential oils, as secondary plant compounds, present a safer alternative to conventional insecticides in insect control programs. So five essential oils including eucalyptus, mint, yarrow, oregano and rosemary oils were evaluated against the brown-banded cockroach Supella longipalpa. Methods: Evaluation was done against the 3rd and 4th instar nymphs using three bioassay methods; continuous contact toxicity, fumigant toxicity and repellent activity. The study was done in the laboratory of medical entomology, during April 2012 to September 2013. Results: Mortality rates by the lowest concentration (2.5%) of rosemary, oregano, yarrow, eucalyptus and mint oils were 100%, 62.2%, 45 %, 36.2% and 5.2% at 24 h after exposure respectively. Rosemary oil was determined as the most toxic oil because of 100 % mortality rate at the concentration range of 2.5% to 30%. The lowest fumigation effect using 50 µl /L air was recorded from mint oil with 97.2 % mortality after 24 h, while the other oils caused 100% mortality. The most repel activity was related to oregano oil which showed 96.5-99.1% repellency at the concentration range of 2.5-30% with a residual effect lasting at least a week after treatment. Conclusion: Oregano oil could be used as a potential repellent against S. longipalpa. Also, all five essential oils could be used as the safe compounds for surface treating or fumigation in cockroach control programs while rosmary and oregano oils exhibited the most toxicity.